DESIGN OF NURUL KALAM GRAND MOSQUE PEMALANG IN CONSTRUCTION MANAGEMENT ASPECT - Prasetia, Rahmandia
does not yet have sufficient capacity to meet the needs of daily worshipers and on holidays. Therefore, it is necessary to build the Nurul Kalam Grand Mosque so that the mosque can fulfill various community activities, not only worship activities, but also educational, social, economic, and recreational activities. The construction of the Nurul Kalam Grand Mosque on aspects of construction management will be reviewed in this Final Project. The scope of the final assignment includes construction methods, calculation of the volume of material requirements, construction scheduling calculations, and estimated construction costs. Performed calculation of volume requirements using Tekla Structure while work productivity calculations using lead sources method for workers and heavy equipment. Calculation of the construction schedule uses Microsoft Project and the calculation of construction costs refers to SNI and PU Candy No. 28. There are four stages of work consisting of preparatory work, earthworks and foundations, upper structural work and landscape work with a total construction cost of Rp94.384.706.736 and a work period of 583 days.